Предмет: Математика,
автор: лия115
упростить 1) (х-1)^2 +(2х+1)^2 ;2)(3-4у)×(4у+3);3)(3-а)×(9+3а+а^2);4)(2а+3)^3
Ответы
Автор ответа:
0
1) х^2-2х+1^2+4х^2+4х+1^2=
=5х^2+2х+2
2)12у+9-16у^2-12у=9-16х^2
3) 27+9а+3а^2-9а-3а^2-а^3=27-а^3
=5х^2+2х+2
2)12у+9-16у^2-12у=9-16х^2
3) 27+9а+3а^2-9а-3а^2-а^3=27-а^3
Похожие вопросы
Предмет: Математика,
автор: nastyapoker2011
Предмет: Биология,
автор: alex29b2008
Предмет: Другие предметы,
автор: filippchikaev
Предмет: Математика,
автор: Dianavip
Предмет: Математика,
автор: ВероникаАлегина